ҚАТЪИЙМАС МАНТИҚ ПРИНЦИПЛАРИ АСОСИДА ТАЛАБАЛАР БИЛИМИНИ КОМПЛЕКС БАҲОЛАШ ТИЗИМИНИ ЯРАТИШ - Калимбетов, К. (SCIENCE and SOCIETY, 2020)
In the given article are considered the principles of system development, of fuzzy estimation of efficiency knowledge of students. The basis of offered system estimation efficiency contains fuzzy numbers, base of knowledge and general circuit of realization experiments.